Restos faunísticos do Crasto de Palheiros (Murça). contributo para o conhecimento da alimentação no calcolítico e na idade do ferro no nordeste português - Cardoso, João Luís (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
We present the results of the study of the faunal remains found on the excavation site of Crasto of Palheiros, dated from the Calcolithic and Iron Age. Both occupations showed no significant differences. By decreasing order of importance, the animals consumed were cows, followed by goats, sheep and finally pigs.